1997
DOI: 10.1292/jvms.59.947
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Findings of Nude Mice Inoculated with Bovine Neospora.

Abstract: ABSTRACT. Nude mice were infested with bovine Neospora by intraperitoneal inoculation of the brain and spinal cord from an aborted bovine fetus due to neosporosis. Inoculated mice showed severe emaciation and tetraplegia at about 2 to 4 months post-inoculation. Histopathologically, polyradiculoneuritis and peripheral neuritis were the major findings, and lesions in the central nervous system were located at periventricular and submeningeal areas of the cerebrum or at the white matter around the roots of radice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0
2

Year Published

1998
1998
2007
2007

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 6 publications
0
9
0
2
Order By: Relevance
“…17 However, some researchers have indicated that Neospora might invade the spinal cord via the spinal nerve and later reach the brain through cerebrospinal fluid. 19 The present results indicate that blood flow might be the main route for parasite spread, because tachyzoites were mainly identified in the endothelial cells of venules or capillaries and spread systemically in a short time.…”
Section: Ifn-␥ Il-4 and Il-6 Production In Jpa1-infected Micementioning
confidence: 55%
See 1 more Smart Citation
“…17 However, some researchers have indicated that Neospora might invade the spinal cord via the spinal nerve and later reach the brain through cerebrospinal fluid. 19 The present results indicate that blood flow might be the main route for parasite spread, because tachyzoites were mainly identified in the endothelial cells of venules or capillaries and spread systemically in a short time.…”
Section: Ifn-␥ Il-4 and Il-6 Production In Jpa1-infected Micementioning
confidence: 55%
“…Athymic nude mice were also useful for isolating the parasite from bovine tissues infected with Neospora. 19,24 Furthermore, interferon (IFN)-␥ knockout mice 14 and mice treated with antibody against IFN-␥ 8 were highly susceptible to Neospora infection and developed severe clinical and pathologic changes. Therefore, cytokines may suppress the propagation of Neospora tachyzoites and may be related to susceptibility to infection.…”
mentioning
confidence: 99%
“…Experimental infection of N. caninum in nude mice has been reported by [17]. In that report, only aggregates of N. caninum tachyzoites but not cysts were observed in the nude mouse brain.…”
Section: Discussionmentioning
confidence: 90%
“…Nude mice inoculated with brain and spinal cord tissue obtained from an aborted fetus infected with N. caninum grew emaciated and tetraplegic with tachyzoites in the inflammatory foci of the peripheral nerves, skeletal muscles, and central nervous system. 12 Tachyzoite densities in the brain tissue of the infected mice were higher than those observed in aborted bovine fetuses or congenitally infected calves. The objective of this study was to use nude mice to propagate and concentrate tachyzoites, increasing the chance of successful isolation of bovine Neospora.…”
mentioning
confidence: 73%